Orthogonal polarization spectral imaging - Cerný, V; Turek, Z; Pařízková, R (Physiological research, 2007)
The microcirculation plays a crucial role in the interaction between blood and tissues both in physiological and pathophysiological states. Despite its critical role in numerous diseases including diabetes, hypertension, sepsis or multiple organ failure, methods for direct visualization and quantitative assessment of human microcirculation at the bedside are limited. Orthogonal polarization spectral (OPS) imaging is a relatively new noninvasive method for assessment of human microcirculation without using fluorescent dyes. Recent clinical studies using OPS imaging in various pathological states have shown a wide spectrum of different clinical applications with evident impact on the diagnosis, treatment or prognosis assessment. Thus, there is a great effort to validate OPS imaging for various clinical purposes. The principles of OPS imaging, validation studies, its advantages, limitations, methods of quantitative assessment and current experience in clinical practice are discussed.
Keywords: Vascular Diseases; Reproducibility of Results; Microscopy, Polarization; Models, Animal; modely u zvířat; nemoci cév; polarizační mikroskopie; mikrocirkulace; Diagnostic Imaging; Animals; lidé; Microcirculation; diagnostické zobrazování; Humans; videomikroskopie; zvířata; reprodukovatelnost výsledků; Microscopy, Video